A Study of Clinical Justice in the Experiences of Patients, Nurses, and Nursing Students: A Qualitative Study - Homa Vejdani; hossein Mohsenipouya; faeze Azadi; Sanaz Fazeli; Arezou Bashghare; Yadollah Jannati; Akram Sanagoo; Leila Jouybari (Kerman University of Medical Sciences, 2021)
Introduction: Reducing healthcare injustice is a moral imperative. People's benefits from these rights differ dramatically from one place to another. Understanding justice in medical care services has created many problems due to ambiguities. The present study aimed to explain the experiences and perspectives of nurses, patients, and nursing students about clinical justice.Methods: This study was a qualitative one based on conventional content analysis. Semi-structured interviews with open-ended questions were used to collect data. Interviews were conducted with clinical nurses, nursing students, and hospitalized patients in hospitals of Behshahr (Mazandaran province). Purposive sampling was used and the interviews continued until data saturation was reached, and finally 73 (19 nursing students, 29 clinical nurses, and 25 hospitalized patients) participants entered the study. Interviews were recorded, and handwritten and then were coded and categorized based on conventional content analysis and themes were extracted.Results: The analysis of data revealed four main themes including "equal treatment", "good manners", "care and attention", and "clinical competence" and 9 subthemes including "ethnic discrimination", "socioeconomic discrimination", "unaccompanied patients", "forgiveness", "respect", "attention to patients' needs/problems", "allocation of sufficient time", "ability to prioritize" and "theoretical and practical competence".Conclusion: The findings of this study suggest that by equal treatment, avoiding ethnic and socioeconomic discrimination, paying attention to the patients' needs and treating them well, and enhancing the level of theoretical and practical skills, it is possible to help create justice in patient care.